2005
DOI: 10.1021/ja053880w
|View full text |Cite
|
Sign up to set email alerts
|

A Proposal for the Mechanism-of-Action of Diazoparaquinone Natural Products

Abstract: The diazoparaquinone family of antibiotics, exemplified by the naturally occurring species prekinamycin (1a), 1 kinamycin F (2), 2 and lomaiviticin A (3), 3 has had a long and storied history, featuring two major structural revisions (N-cyanocarbazole → diazofluorene for the kinamycins, 4 and diazobenzo [b]fluorene → diazobenz[a]-fluorene for isoprekinamycin (not shown) 5 ). Following these corrections, two mechanism-of-action hypotheses have been proposed. Jebaratnam, using diazofluorene as a model system, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…While it has been shown that the kinamycin analog prekinamycin forms radical-trapping arene products that involved the loss of dinitrogen in organic aromatic solvents containing a radical initiator and an organic tin reducing agent [8,9], the non-physiological conditions of these studies make direct comparisons with our study problematic.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…While it has been shown that the kinamycin analog prekinamycin forms radical-trapping arene products that involved the loss of dinitrogen in organic aromatic solvents containing a radical initiator and an organic tin reducing agent [8,9], the non-physiological conditions of these studies make direct comparisons with our study problematic.…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies on prekinamycin, a precursor analog of kinamycin, showed that in aromatic solvents containing a radical initiator and an organic tin reducing agent, radical-trapping arene products were formed that involved the loss of dinitrogen to form a postulated reactive radical intermediate and an orthoquinonemethide electrophile [8,9]. A role for reductive activation of kinamycin D by DTT in its DNA-cleaving ability has also recently been suggested [10].…”
Section: Introductionmentioning
confidence: 99%
“…While kinamycin C has been subjected to the 60-cell National Cancer Institute panel, kinamycin A has not. More recently prekinamycin, a precursor analog of kinamycin, was shown to form a phenyl adduct in the presence of a mild organic reductant and a radical initiator in benzene [6]. The kinamycins were initially assigned an N-cyanocarbazole structure and it was initially thought that, due to similarities of the indoloquinone system to that of the clinical antitumor agent mitomycin C, the kinamycins likely functioned as reductively activated DNA alkylating agents by a mechanism related to that for the mitomycins [3].…”
Section: Introductionmentioning
confidence: 99%
“…In the 60-cell panel, kinamycin C generally displayed submicromolar GI 50 values (http://dtp.nci.nih.gov). Prekinamycin was proposed to undergo a two-step mechanism involving loss of dinitrogen to form a reactive radical intermediate that could damage biological components [6]. We [4] and another group [5], however, independently determined that the structures assigned to the kinamycins were incorrect, and that the kinamycins are in fact derivatives of diazobenzo [b]fluorene, rather than of Ncyanobenzo[b]carbazole.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] This loss of dinitrogen is probably initiated by a one-electron addition to the p-quinone. [12] Lomaiviticins A (9) and B (10) are particularly interesting dimeric compounds, as they show very potent antitumor activity, in addition to antibacterial activity against Staphylococcus aureus. [13] The novel structures and antitumor activities of the kinamycins have stimulated the interest for the development of their total synthesis.…”
Section: Introductionmentioning
confidence: 99%